Description of a new genus and three new species of Otothyrinae (Siluriformes, Loricariidae) - Roxo, Fabio F. [UNESP]; Silva, Gabriel S. C. [UNESP]; Ochoa, Luz E. [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publ, 2015)
The genus Hisonotus was resurrected as a member of the tribe Otothyrini (actually subfamily Otothyrinae). However, phylogenetic studies based on morphological and molecular data showed that Hisonotus is not monophyletic and independent lineages can be identified, such as the group composed of the species H. insperatus, H. luteofrenatus, H. oliveirai, H. paresi and H. piracanjuba, a lineage unrelated to that containing the type species of the genus Hisonotus (H. notatus). Herein, based in molecular and morphological data, a new genus is described to accommodate the lineage mentioned above, into which are also added three new species. This new genus can be distinguished from other genera of Otothyrinae by the following combination of characters: (1) a pair of rostral plates at the tip of the snout; (2) two large pre-nasal plates just posterior to the rostral plates; (3) a supra-opercular plate that receives the laterosensory canal from the compound pterotic before the preopercle; (4) a well developed membrane at anal opening in females; and (5) a V-shaped spinelet. A key to species of Curculionichthys is provided.
Keywords: Cascudinhos; freshwater fishes; systematic; Hisonotus; taxonomy